Teleconsultation in respiratory medicine – A position paper of the Portuguese Pulmonology Society - Morais, A (2022)
The COVID-19 pandemic crisis, among so many social, economic and health problems, also brought new opportunities. The potential of telemedicine to improve health outcomes had already been recognised in the last decades, but the pandemic crisis has accelerated the digital revolution. In 2020, a rapid increase in the use of remote consultations occurred due to the need to reduce attendance and overcrowding in outpatient clinics. However, the benefit of their use extends beyond the pandemic crisis, as an important tool to improve both the efficiency and capacity of future healthcare systems. This article reviews the literature regarding telemedicine and teleconsultation standards and recommendations, collects opinions of Portuguese experts in respiratory medicine and provides guidance in teleconsultation practices for Pulmonologists.